The Importance of Indirect Taxes in the Architecture of Tax Systems in Some EU Member States - Nicoleta STANCIU ANGHELUŢĂ; George UNGUREANU (Communications of International Proceedings, 2021)
The paper aims to analyze the fiscal policy and indirect taxes in the member countries of the European Union and Romania, because no state is willing to give up the right to collect taxes from its citizens in the way it wants. This study aims to highlight the importance of indirect taxes as well as their impact on the income of the population balanced with the impact of indirect taxes collected on state budgets. The paper presents the evolution of these taxes for the period 2017-2019, as well as the close link between values added tax and gross domestic product. In most countries of the world, indirect taxes occupy a predominant place in the total fiscal resources. The main indirect taxes are value added tax, excise duties and customs duties. In some countries, the system of indirect taxation also includes real estate tax, taxes on the use of natural resources, road taxes and others, established according to the fiscal policy promoted by the state. The fiscal system can be used as a tool to regulate economic life, state intervention in the economy by eliminating imbalances in different periods of economic life. The relationship between taxation and the level of development of the economy is conditioned in the sense that a stable and developed economy always reflects an environment conducive to fiscal flexibility (reducing budgetary pressure has no effect on economic development due to the tendency of economic operators to divert additional revenues from the economic circuit).
Keywords: Fiscal Policy; Taxes; Evolution; Taxpayers; Impact.